2012
DOI: 10.1039/c2cs35082c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the complexity of aerosol particle properties and processes using single particle techniques

Abstract: The complex interplay of processes that govern the size, composition, phase and morphology of aerosol particles in the atmosphere is challenging to understand and model. Measurements on single aerosol particles (2 to 100 μm in diameter) held in electrodynamic, optical and acoustic traps or deposited on a surface can allow the individual processes to be studied in isolation under controlled laboratory conditions. In particular, measurements can now be made of particle size with unprecedented accuracy (sub-nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
458
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 338 publications
(465 citation statements)
references
References 241 publications
7
458
0
Order By: Relevance
“…As a robust methodology for the levitation of single particles which carry electric charge, the electrodynamic balance (EDB) technique has been applied in atmosphere science for several decades (see reviews by Davis, 1997;Krieger et al, 2012). On the base of such a strategy, numerous studies have been carried out on aerosol particles and droplets, including but not limited to contact ion pairs formation (e.g.…”
Section: H-j Tong Et Al: a New Electrodynamic Balance (Edb) Designmentioning
confidence: 99%
“…As a robust methodology for the levitation of single particles which carry electric charge, the electrodynamic balance (EDB) technique has been applied in atmosphere science for several decades (see reviews by Davis, 1997;Krieger et al, 2012). On the base of such a strategy, numerous studies have been carried out on aerosol particles and droplets, including but not limited to contact ion pairs formation (e.g.…”
Section: H-j Tong Et Al: a New Electrodynamic Balance (Edb) Designmentioning
confidence: 99%
“…Studies on single particles, confined within optical or electrodynamic traps, now provide precise measurements of aerosol refractive indices and phases, hygroscopic growth, evaporation of semi-volatile components, and other properties of importance for their atmospheric behaviour. [2][3][4][5][6] These trapping-based techniques are most applicable to single particles with radii greater than 1 μm, but the smaller accumulation mode particles are of greater significance for atmospheric processes. 4 In a recent publication, we demonstrated that absolute extinction cross sections for single submicron radius spherical aerosol particles can be measured with high precision by combining optical confinement and levitation of a particle with cavity ring-down spectroscopy (CRDS).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] These trapping-based techniques are most applicable to single particles with radii greater than 1 μm, but the smaller accumulation mode particles are of greater significance for atmospheric processes. 4 In a recent publication, we demonstrated that absolute extinction cross sections for single submicron radius spherical aerosol particles can be measured with high precision by combining optical confinement and levitation of a particle with cavity ring-down spectroscopy (CRDS). 7 The change in ring-down time (RDT) when a particle is moved from well below the optical axis (z) of the ring-down cavity (RDT = 0) to the height of the centre axis of the Gaussian TEM00 cavity mode (RDT = ) is given by:…”
Section: Introductionmentioning
confidence: 99%
“…23−25 To address the challenges in quantifying hygroscopicity for aerosols of complex composition, refinements in laboratory and field instrumentation, and improved frameworks for representing hygroscopicity, are required. 26,27 Hygroscopic growth measurements must be made up to water activities close to the dilute limit, ideally as high as 0.999. Such high water activities (a w ) are required for measurements to be directly relevant to CCN activation 28 and to place tighter constraints on the equilibrium solution compositions required to underpin the development of predictive models.…”
Section: Introductionmentioning
confidence: 99%